Pengaruh Store Atmosphere Kualitas Produk dan Harga Terhadap Keputusan Pembelian Pada Art Shop Surya Silver di Gianyar - Krisna, I Putu Gede Haradha; Suartina, I Wayan; Wulandari, Ni Luh Adisti Abiyoga (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
The existence of tourists' interest in silver works of art, makes companies compete in offering silver products. Product quality is one of the considerations of consumers in deciding to buy a product. A good store design will attract consumer desires. Another aspect that consumers consider when visiting a Perak art shop is to consider the price. The formulation of the problem and the purpose of this study was to determine the effect of store atmosphere, product quality and price on purchasing decisions. The sample used was 34 respondents. The data analysis technique used is Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t Test and F Test. Based on the results of the study it can be seen that: (1) store atmosphere has a significant positive effect on purchasing decisions, where the t value is obtained 2.877 and sig 0.005. (2) product quality has a significant positive effect on purchasing decisions, where the t value is 3.316 and sig 0.001. (3) price has a significant positive effect on purchasing decisions, where the t value is 3.025 and sig is 0.003. (4) simultaneously store atmosphere, product quality and price have a significant effect on purchasing decisions, where the F value is 38.133 and the significance is 0.000. The magnitude of the influence of independent variables on purchasing decisions is 53.2%.